2016
DOI: 10.1161/strokeaha.116.013879
|View full text |Cite
|
Sign up to set email alerts
|

Good Intracranial Collaterals Trump Poor ASPECTS (Alberta Stroke Program Early CT Score) for Intravenous Thrombolysis in Anterior Circulation Acute Ischemic Stroke

Abstract: Two independent neuroradiologists determined their ASPECTS. We stratified patients using ASPECTS into 2 groups: large volume infarcts (ASPECTS≤7 points) and small volume infarcts . In addition, we evaluated a third group with very large volume infarcts (ASPECTS≤5 points). We then analyzed the 3 subgroups using the Maas, Tan, and ASPECTS-collaterals grading systems of the computed tomographic angiogram intracranial collaterals. Good outcomes were defined by modified Rankin Scale score of 0 to 2 at 3 months. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 24 publications
2
55
0
1
Order By: Relevance
“…The degree of such collateral blood supply varies amongst individuals and can influence outcomes, especially in patients with AIS due to LVO [16]. Patients with good collateral flow demonstrated less hypoperfused tissue, less infarct growth within the penumbra zone, and smaller infarct volumes with better outcomes than those with poor collaterals [17]. Our study found that elevated IGF2 and LYVE1 levels and lower THBS1 levels were associated with better collateral circulation in patients with AIS due to LVO.…”
Section: Discussionmentioning
confidence: 78%
“…The degree of such collateral blood supply varies amongst individuals and can influence outcomes, especially in patients with AIS due to LVO [16]. Patients with good collateral flow demonstrated less hypoperfused tissue, less infarct growth within the penumbra zone, and smaller infarct volumes with better outcomes than those with poor collaterals [17]. Our study found that elevated IGF2 and LYVE1 levels and lower THBS1 levels were associated with better collateral circulation in patients with AIS due to LVO.…”
Section: Discussionmentioning
confidence: 78%
“…Traditional non-invasive evaluation of collateral status has focused primarily on interpretation of CTA techniques. Several scales have been developed to assess collateral status on CTA based on the degree of contrast opacification of the MCA vessels distal to the site of occlusion [25][26][27]. Patients with a robust filling of arteries distal to the site of occlusion on CTA are deemed to have favorable collaterals [25].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research indicated that good collaterals may trump poor ASPECTS when considering patients with low ASPECTS for intravenous lysis 10. Moreover, poor collaterals have been demonstrated to be strong predictors of an unfavorable response to MT and functional outcome 11–13.…”
Section: Introductionmentioning
confidence: 99%